LEGAL PROTECTION OF PERSONAL DATA OF INDONESIAN CITIZENS BASED ON ACT NUMBER 27 OF 2022 - Ni Made Dwi Gayatri Putri; Dewa Gede Wibhi Girinatha (NOTARIIL Jurnal Kenotariatan, 2024)
The purpose of this research is to analyze personal data, which is private and must be protected. Numerous cases of personal data breaches in Indonesia have had detrimental effects on society. The lack of comprehensive legislation results in inadequate legal protection against data breaches. Due to the frequent occurrence of personal data breaches, the government enacted the Personal Data Protection Law Number 27 of 2022. This research employs normative methods with a legislative and conceptual approach. The findings reveal that legal protection against personal data breaches is comprehensive under Law Number 27 of 2022. Preventive efforts to protect personal data include not sharing data by the public and avoiding illegal platforms prone to cybercrime. There is also a need for public awareness to safeguard personal data. Meanwhile, the government will conduct compliance testing and take repressive protective measures. If a personal data breach occurs, the sanctions outlined in the Personal Data Protection Law include criminal penalties under Articles 67 and 68, which stipulate fines and imprisonment, and Article 70 for corporate violations.